Impaired production of skin barrier lipid acylceramides and abnormal localization of PNPLA1 due to ichthyosis-causing mutations in PNPLA1. Issue 2 (August 2022) - Nohara, Tomohiro; Ohno, Yusuke; Kihara, Akio
Abstract: Background: PNPLA1 is a causative gene of autosomal recessive congenital ichthyosis. The transacylase PNPLA1 produces ω- O -acylceramides (acylceramides), lipids essential for the skin barrier function, by catalyzing the transfer of a linoleic acid from triglycerides to ω-hydroxyceramides. Objective: We aimed to validate the involvement of PNPLA1 mutations found in ichthyosis patients in the pathogenesis and elucidate the correlation between the effects of these mutations on acylceramide-producing activity and ichthyosis pathology. Methods: Acylceramide-producing activity of PNPLA1 mutants was investigated using a cell-based assay system, in which wild-type PNPLA1 or each PNPLA1 mutant was co-overexpressed with the enzymes involved in acylceramide synthesis. The effect of each mutation on the ABHD5-dependent lipid droplet localization of PNPLA1 was examined through indirect immunofluorescence microscopy. Results: Of 16 PNPLA1 missense mutations, 15 mutations, except the C216R mutation, resulted in a complete loss of acylceramide-producing activity, while the C216R mutation weakly affected this activity. Intracellular localization of mutants with no activity varied among mutants. Two mutants (S19L and D172N) localized in lipid droplets, and eight mutants (S53L, S53W, A59V, T125N, D129E, R166C, P234S, and P235L) partially localized there. Five mutants (A34P, A34T, S53P, K141E, and P163L) localized throughout the cytosol. Conclusion: The PNPLA1 missense mutations examined in this study are responsible for ichthyosis pathology. The weak effect of C216R mutation on acylceramide-producing activity correlates with the mild symptoms of the ichthyosis patient. Sixteen PNPLA1 mutants were classified into four groups based on their acylceramide-producing activity and localization. Highlights: Most PNPLA1 ichthyosis mutations abolish acylceramide-producing activity. C216R mutation weakly affects acylceramide-producing activity. Effects on the lipid droplet localization of PNPLA1 vary among the mutations. PNPLA1 mutants can be classified into four groups based on activity and localization.